Experimental Study of Onset of Nucleate Boiling in Vertical Rectangular Channels with Different Flow Path Heights - Ning Cheng; Shuwen Yu; Jun Xiao; Chang-Hong Peng (Science and Technology of Nuclear Installations)
A study on ONB (onset of nucleate boiling) in two vertical rectangular channels are experimentally conducted in a range of mass flux varying from 100 to 300 kg/(m2·s), inlet water temperature from 70 to 100°C, heat flux from 10 to 70 kW/m2, and local pressure of 0.145 MPa. The cross-section sizes are 1.8 mm ∗ 60 mm and 2.8 mm ∗ 60 mm, respectively. Three boiling incipience judgment methods have been used to locate ONB sites and found that ΔTONB (the wall superheat at ONB site) increases with the decrease of inlet temperature and increases as mass flux increases. The results also indicate that although the bubble size and behaviors in the narrow channel are different from that in the nonnarrow channel at the ONB site, the heat transfer has not been influenced evidently. In addition, ΔTONB in both channels can be predicted by the correlation proposed by Thom within the error range of ±30%.